Production of Purpureocillium lilacinum and Pochonia chlamydosporia by submerged fermentation, and their effects on Tetranychus urticae and Heterodera glycines through seed inoculation of common beans plants - Silva, Daniela Milanez (2020)
The filamentous fungi Pochonia chlamydosporia (Hypocreales: Clavicipitaceae) and Purpureocillium lilacinum (Hypocreales: Ophiocordycipitaceae) are commonly found in soils and vegetations. Microesclerotia is resistant structures with potential for use in seed treatments aiming to control aboveground diseases and pests, as well as improving plant growth. Thus, this study aimed to investigate the ability of P. lilacinum and P. chlamydosporia to promote common bean (Phaseolus vulgaris) growth and to suppress populations of Tetranychus urticae and Heterodera glycines, through seed treatment. Initially, a screening with 37 Brazilian isolates of P. lilacinum and 2 isolates of P. chlamydosporia was carried outto evaluate the microsclerotia production in three culture media. All isolates produced microsclerotia and submerged propagules. The best isolates produced > 104 microsclerotia ml-1. In addition, a high concentration of submerged propagules (conidia and blastospores) was observed for most isolates (above 109 propagules ml-1). The P. lilacinum isolates ESALQ1744, ESALQ2482, and ESALQ2593, and P. chlamydosporia ESALQ5405 and ESALQ5406 were selected for the studies on plants. Overall, common bean plants inoculated with P. lilacinum and P. chlamydosporia did not differ from non-inoculated plants regarding the vegetative parameters, except for the dry weight of roots in the second experiments, where all the isolates were superior to the non-inoculated control. The population density of cystoid nematodes was similar among the treated plants and the uninoculated ones, except for the third experiment in which the plants inoculated with isolate ESALQ5406 presented lower densities than the control. However, for nematodes per root weight, it was observed lower population densities in fungal treated plants ESALQ5406 and ESALQ2593 at the second experiment. A reduction in populations of the two-spotted mite in fungi-treated plants was observed for all isolates. Although aerial conidia of P. lilacinum and P. chlamydosporia has been used for the control of nematodes, in this study it was demonstrated that these two fungal species also have the potential for the management of pests of the aerial part through bean seed treatment with microsclerotia.